Alpha-Linolenic and Linoleic Acid Status of Broilers Kept on Small Holdings in Cameroon - Hovenier, R.; Teguia, A.; Beynen, A.C. (International Journal of Poultry Science, 2006)
The idea tested was that a limiting provision of alpha-linolenic acid (ALA) contributes to the poor growth performance of broilers kept on small holdings in Cameroon. The study had a cross-sectional design and involved 14 small-holder farms. The ALA and linoleic acid (LA) concentrations in the broilers` diets were determined and so were the contents of ALA and LA in adipose tissue collected from selected birds. When expressed as percentage in the whole diet, the LA content in the diets fed on the 14 farms varied between 1.64 and 3.81 % and that of ALA between 0.04 and 0.41%. There was a significant relationship between the relative percentage of ALA in the diet and that in the abdominal adipose tissue of the broilers. It was concluded that the LA supply was not limiting growth in the broilers. The ALA requirement of broilers is not known, but it might be in the order of 0.05 to 0.1 % of the dietary dry matter. If and when the ALA requirement is 0.05% of the diet, then the supply of ALA on at least one farm could have limited growth of the broilers. However, caution is warranted because the design of this study does not allow drawing conclusions as to cause-and-effect relations. Furthermore, on all farms growth rates were sub-optimal so that factors other than the ALA supply had limited growth. Absolute proof for a role of the ALA supply can only be obtained by controlled studies on the farms in which supplemental ALA is the only variable.